EFFECT OF GRANTING LIFE REVIEW THERAPY TO DEPRESSION LEVEL ON LANSIA IN PANTI WERDHA MOJOPAHIT MOJOKERTO - Yani, Athi Linda; Febiansyah, Afrizal afri (STIKes Maharani Malang, 2018)
Depression is a form of mental disturbance in the nature of feelings (affective, mood) characterized by moodiness, sadness, lethargy, loss of passion, no spirit, and feeling helpless, useless, and desperate. This research uses Quasy Experiment method with Pretest Postest control group design. With the sample number of 20 respondents (2 groups) using Purposive Sampling technique. The data were collected by questionnaire method and then tabulated by using frequency distribution and test using Wilcoxon test with significance level α = 0.05 The results of the study in the treatment group showed the depression level before the treatment of respondents who suffered severe depression 10 people (100%). After treatment of respondents who were depressed moderate 5 people (50%) and mild depression 5%. Based on Wilcoxon test in treatment group is found P = 0,042 (<0,05) and Mann-Whitney test in post is found P = 0,008 (<0,05). This shows that the value of P <0.05. So there is a difference between the control group and the treatment. The conclusion that can be taken from this research is there is a significant influence of Life Review Therapy on the level of depression in elderly. From these results, with the provision of Life Review Therapy can be used to reduce the level of depression.